2021
DOI: 10.20517/cdr.2021.78
|View full text |Cite
|
Sign up to set email alerts
|

Using cfRNA as a tool to evaluate clinical treatment outcomes in patients with metastatic lung cancers and other tumors

Abstract: Aim: We report an exploratory analysis of cfRNA as a biomarker to monitor clinical responses in non-small cell lung cancer (NSCLC), breast cancer, and colorectal cancer (CRC). An analysis of cfRNA as a method for measuring PD-L1 expression with comparison to clinical responses was also performed in the NSCLC cohort. Methods: Blood samples were collected from 127 patients with metastatic disease that were undergoing therapy, 52 with NSCLC, 50 with breast cancer, and 25 with CRC. cfRNA was purified from fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 29 publications
(43 reference statements)
0
12
0
Order By: Relevance
“…ctDNA profiling is now being routinely applied clinically for both companion diagnosis and screening for minimal residual disease (MRD) among cancer patients. However, the detection of ctDNA for MRD is challenging as only a minute amount of ctDNA are present in blood at earlier cancer stages, especially in post-surgical setting ( 7 , 10 , 50 ). The cfDNA concentration may fall below the detection limit of the NGS-based ctDNA test, resulting in a very low or even zero mutation allele frequency (MAF) for the mutations ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ctDNA profiling is now being routinely applied clinically for both companion diagnosis and screening for minimal residual disease (MRD) among cancer patients. However, the detection of ctDNA for MRD is challenging as only a minute amount of ctDNA are present in blood at earlier cancer stages, especially in post-surgical setting ( 7 , 10 , 50 ). The cfDNA concentration may fall below the detection limit of the NGS-based ctDNA test, resulting in a very low or even zero mutation allele frequency (MAF) for the mutations ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…The cfDNA concentration may fall below the detection limit of the NGS-based ctDNA test, resulting in a very low or even zero mutation allele frequency (MAF) for the mutations ( 51 ). More importantly, it is difficult to determine the tumor tissue of origin (TOO) in cancer patients and differentiate informative cfDNA mutations from benign variants such as clonal hematopoiesis ( 7 ). Therefore through the amplification of tumor-derived RNA signal, we have shown that the detection of the expressed cfRNA in blood is technically feasible and may help circumvent the existing limitation in ctDNA detection, which will increase cancer detection sensitivity ( 7 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 1990s, the Human Genome Project demonstrated that cf DNA has tumor-specific mutations. Most of the cancer research was focused on cf DNA as compared to cf RNA because of its stability and detectability; however, numerous studies have speculated that cf RNA may have more potential compared to cf DNA [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%